The effect of structured medication review followed by face-to-face feedback to prescribers on adverse drug events recognition and prevention in older inpatients – a multicenter interrupted time series study - Joanna E. Klopotowska; Paul F. M. Kuks; Peter C. Wierenga; Clementine C. M. Stuijt; Lambertus Arisz; Marcel G. W. Dijkgraaf; Nicolette de Keizer; Susanne M. Smorenburg; Sophia E. de Rooij; on behalf of the WINGS Study Group (BMC Geriatrics, 2022)
Abstract Background The effectiveness of interventions to improve medication safety in older inpatients is unclear, given a paucity of properly designed intervention studies applying clinically relevant endpoints such as hospital-acquired preventable Adverse Drug Events (pADEs) and unrecognized Adverse Drug Events (uADEs). Therefore, we conducted a quality improvement study and used hospital-acquired pADEs and uADEs as main outcomes to assess the effect of an intervention aimed to improve medication safety in older inpatients. Method The study followed an interrupted time series design and consisted of three equally spaced sampling points during baseline and during intervention measurements. Each sampling point included between 80 to 90 patients. A total of 500 inpatients ≥65 years and admitted to internal medicine wards of three Dutch hospitals were included. An expert team retrospectively identified and assessed ADEs via a structured patient chart review. The findings from baseline measurement and meetings with the internal medicine and hospital pharmacy staff were used to design the intervention. The intervention consisted of a structured medication review by hospital pharmacists, followed by face-to-face feedback to prescribers, on average 3 days per week. Results The rate of hospital-acquired pADEs per 100 hospitalizations was reduced by 50.6% (difference 16.8, 95% confidence interval (CI): 9.0 to 24.6, P <  0.001), serious hospital-acquired pADEs by 62.7% (difference 12.8, 95% CI: 6.4 to 19.2, P <  0.001), and uADEs by 51.8% (difference 11.2, 95% CI: 4.4 to 18.0, P <  0.001). Additional analyses confirmed the robustness of the intervention effect, but residual bias cannot be excluded. Conclusions The intervention significantly decreased the overall and serious hospital-acquired pADE occurrence in older inpatients, and significantly improved overall ADE recognition by prescribers. Trial registration International Standard Randomized Controlled Trial Number Register, trial registration number: ISRCTN64974377 , registration date (date assigned): 07/02/2011.